IVAN KOCHERHA - THE THEORIST OF DRAMATIC ART - Khorob, Stepan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The Aim. The article systematically examines the views of the Ukrainian playwright Ivan Kocherha (1881–1952) on the nature and specificity of drama as a kind of literature and art form. His understanding of the time and space organization of a dramatic work, genre creation and plot structure is revealed, as well as his interpretation of such important ideological and aesthetic categories for the theory of drama as dramatic action, dramatic conflict, drama, stagecraft, etc. Not only the self-worth of Ivan Kocherha’s literary and theater studies has been proven, but also their topicality in the study of the aesthetics and poetics of drama in our time. In accordance with the set goal and system of tasks, the following methodological approaches are proposed in their solution: concrete-historical, philological, hermeneutic. This gave grounds to study the literary and critical heritage of the Ukrainian playwright Ivan Kocherha as a literary phenomenon that contributes to the elucidation of important categories of dramatic poetics both at the theoretical and historical-literary levels. The scientific novelty of the research lies in the comprehensive understanding of Ivan Kocherha’s literary concepts in the light of modern drama theory. Therefore, new views on the problem of "Kocherha as a theorist of drama" have practical significance: the results of the study can be used both in academic studies on Ukrainian dramatic art, and in works about the dramatist and his plays studied in secondary and higher schools of Ukraine.